2016
DOI: 10.1177/0004865815604195
|View full text |Cite
|
Sign up to set email alerts
|

Improving the law reform process: Opportunities for empirical qualitative research?

Abstract: Research on law reform has identified a variety of factors that help or hinder the reform process, but it has not systematically explored the role that empirical research plays and could play in enabling and enhancing law reform. Drawing on a series of qualitative interviews with criminal law reform experts in Victoria, we analyse the current uses and perceived value of empirical research in criminal law reform and explore opportunities for qualitative research methods to be used more systematically or extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The present study extends qualitative research on reasonable belief in consent in rape law by providing insight into community and professional perceptions of the adequacy and scope of this legal definition of rape – both on the books and in practice. 2 The FGDs reported in this article were one element of a broader, mixed-method study of perceptions regarding the adoption of an objective fault element for rape in the Australian state of Victoria (see Hanley et al, 2015; Larcombe et al, 2015). 3 Legal and sexual assault professionals and community stakeholders were recruited to participate in the FGDs and an associated survey through direct invitations from the research team members and separate advertisements (for each group type) distributed in a range of professional networks and media, including mailing lists for sexual assault and women’s health services, mailing lists for legal organizations, notices in community newsletters, circulation through peak bodies and postings on social media (Facebook and Twitter).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study extends qualitative research on reasonable belief in consent in rape law by providing insight into community and professional perceptions of the adequacy and scope of this legal definition of rape – both on the books and in practice. 2 The FGDs reported in this article were one element of a broader, mixed-method study of perceptions regarding the adoption of an objective fault element for rape in the Australian state of Victoria (see Hanley et al, 2015; Larcombe et al, 2015). 3 Legal and sexual assault professionals and community stakeholders were recruited to participate in the FGDs and an associated survey through direct invitations from the research team members and separate advertisements (for each group type) distributed in a range of professional networks and media, including mailing lists for sexual assault and women’s health services, mailing lists for legal organizations, notices in community newsletters, circulation through peak bodies and postings on social media (Facebook and Twitter).…”
Section: Methodsmentioning
confidence: 99%
“…Our study also revealed that there is an untapped interest among sexual assault professionals and community members in contributing to research and thinking about rape law reform. It would be ideal if this interest were tapped in advance of future law reform (see Hanley et al, 2015).…”
Section: Further Rape Law Reformmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, little is known about the process surrounding 'consultation'-commonly used language in law reform processes on violence against women-and the outcomes associated with recommendations and subsequent policy development and law reform proposals. Research into law reform focuses on participation rather than listening in decision-making processes (Nheu and McDonald 2010); the use made of empirical research and the quality of empirical research undertaken (Brereton 1994;Hanley et al 2016); how feminists negotiate law reform processes (Scutt 1985;Featherstone 2017); and evaluating the effectiveness of law reform (Douglas 2012;Fitzgibbon and Stubbs 2012;Morgan 2012;Mason 2021). It is vital to investigate the listening interface between women's voices, law reform processes and recommendations, and parliamentary and public policy responses, to improve the quality and effect of law reform and policy addressing violence against women.…”
Section: Women's Voices and Listening In Law Reform On Violence Again...mentioning
confidence: 99%